Draft Genome Sequence of Fusarium oxysporum f. sp. cubense Tropical Race 4 from Peru, obtained by nanopore and illumina hybrid assembly - Leiva Sandoval, Ana Maria; Rouard, Mathieu; López Alvarez, Diana; Cenci, Alberto; Breton, Catherine; Acuña, Rosalyn; Rojas, Juan Carlos; Dita Rodriguez, Miguel Angel; Cuéllar, Wilmer Jose (American Society for Microbiology, 2022)
Fusarium oxysporum f. sp. cubense tropical race 4 (Foc TR4) is the causal agent of Fusarium wilt, a major threat to the banana industry worldwide. Here, we report the genome of a Foc TR4 strain from Peru, sequenced using a combination of Illumina and Oxford Nanopore Technologies.